Field notes by Richard Nicholson, December 19, 1981 - Nicholson, Robertet al (1981)
Field notes by Richard Nicholson with sighting information for a Bohemian Waxwing, Red Crossbill, Prairie Falcon, and Cooper's Hawk. This document is the back page of a documentation form reviewed by the Records Committee: https://avian.lib.iastate.edu/documents/619/view Epson - sheet feed